Hepatoprotective Effect of the Ethanol Extract of Illicium henryi against Acute Liver Injury in Mice Induced by Lipopolysaccharide - Md Sodrul Islam; Hui Yu; Lingyan Miao; Zhaoying Liu; Yanfei He; Hongxiang Sun (MDPI AG, 2019)
The root bark of Illicium henryi has been used in traditional Chinese medicine to treat lumbar muscle strain and rheumatic pain. Its ethanol extract (EEIH) has been previously reported to attenuate lipopolysaccharide (LPS)-induced acute kidney injury in mice. The present study aimed to evaluate the in vitro antioxidant activities and in vivo protective effects of EEIH against LPS-induced acute liver injury (ALI) in mice as well as explore its molecular mechanisms. The mice were injected intraperitoneally (i.p.) with EEIH at the doses of 1.25, 2.5, and 5.0 mg/kg every day for 5 days. One hour after the last administration, the mice were administered i.p. with LPS (8 mg/kg). After fasting for 12 h, blood and liver tissues were collected to histopathological observation, biochemical assay, enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (qRT-PCR), and Western blot analyses. EEIH possessed 2,2-diphenyl-1-picrylhydrazil (DPPH) and 2,2′-azino-bis-(3-ethylbenzothiozoline-6-sulfonic acid) disodium salt (ABTS) radical scavenging activities and ferric-reducing antioxidant capacity in vitro. The histopathological examination, serum biochemical analysis, and liver myeloperoxidase (MPO) activity showed that EEIH pretreatment alleviated LPS-induced liver injury in mice. EEIH significantly dose-dependently decreased the mRNA and protein expression levels of inflammatory factors TNF-α, IL-1β, IL-6, and COX-2 in liver tissue of LPS-induced ALI mice via downregulating the mRNA and protein expressions of toll-like receptor 4 (TLR4) and inhibiting the phosphorylation of nuclear factor-κB (NF-κB) p65. Furthermore, EEIH markedly ameliorated liver oxidative and nitrosative stress burden in LPS-treated mice through reducing the content of thiobarbituric acid reactive substances (TBARS), inducible nitric oxide synthase (iNOS), and nitric oxide (NO) levels, restoring the decreased superoxide dismutase (SOD) and reduced glutathione (GSH) levels, and up-regulating nuclear factor erythroid 2 related factor 2 (Nrf2). These results demonstrate that EEIH has protective effects against ALI in mice via alleviating inflammatory response, oxidative and nitrosative stress burden through activating the Nrf2 and suppressing the TLR4/NF-κB signaling pathways. The hepatoprotective activity of EEIH might be attributed to the flavonoid compounds such as catechin (1), 3′,4′,7-trihydroxyflavone (2), and taxifolin (7) that most possibly act synergistically.